2009
DOI: 10.1007/s11899-009-0023-4
|View full text |Cite
|
Sign up to set email alerts
|

Infant acute lymphoblastic leukemia: Lessons learned and future directions

Abstract: Compared with acute lymphoblastic leukemia (ALL) in older children, ALL in infants has a dismal outcome because rearrangements of the mixed-lineage leukemia (MLL) gene occur in about 80% of these patients, leading to an aggressive type of leukemia. With most recent therapies, about 50% long-term event-free survival is achieved, but early bone marrow relapse remains a major problem. Early intensification of chemotherapy and new innovative therapies are necessary to improve outcome. Bone marrow transplantation s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
3
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(61 citation statements)
references
References 47 publications
2
54
3
2
Order By: Relevance
“…One of the most frequently used genetic aberrations is the Ph chromosome, also termed the BCR-ABL fusion gene, which may indicate a poor prognosis (36,37). The present investigation of the Ph chromosome based on 509 Chinese patients found that the incidence of the Ph chromosome was 17.68%, with no significant difference between the genders (P=0.931).…”
Section: Median Age ------------------------------------------------mentioning
confidence: 59%
“…One of the most frequently used genetic aberrations is the Ph chromosome, also termed the BCR-ABL fusion gene, which may indicate a poor prognosis (36,37). The present investigation of the Ph chromosome based on 509 Chinese patients found that the incidence of the Ph chromosome was 17.68%, with no significant difference between the genders (P=0.931).…”
Section: Median Age ------------------------------------------------mentioning
confidence: 59%
“…26 Therefore, we postulated that the identified list of hypomethylated and highly expressed genes (Figure 1), including several known proto-oncogenes, may represent potential targets for therapeutic intervention. As currently no straightforward approaches have been identified to target hypomethylated genes, we set out to indirectly apply connectivity mapping 15,19,27 on hypomethylated genes originally identified by high-throughput DNA methylation profiling ( Figure 1).…”
Section: Connectivity Map Analysis On a T(4;11)-positive Hypomethylatmentioning
confidence: 99%
“…However some genetic changes altering the expressions of hematopoietic transcription factors are suspected to be responsible for the malignant transformation [164] (for more detailed information about characteristics of ALL, please see reviews [165] and [166]). A recent report showed that membrane-bound sialidase, an enzyme responsible for the degradation of gangliosides, was downregulated in ALL; and when sialidase was overexpressed, apoptotic induction was obtained with the concomitant increase in ceramide levels and decrease in lactosylceramide [167].…”
Section: Targeting Sphingolipid Metabolism For the Treatment Of Leukementioning
confidence: 99%